Evaluation of Extended Interval Dosing Aminoglycosides in the Morbidly Obese Population - Ashley L. Ross; Jennifer L. Tharp; Gerald R. Hobbs; Richard McKnight; Aaron Cumpston (Advances in Pharmacological Sciences)
Aminoglycoside dosing has been studied in the obese population, typically recommending an adjusted weight utilizing a 40% dosing weight correction factor (IBW + 0.4 × (TBW–IBW)). These studies included limited numbers of morbidly obese patients and were not done in the era of extended interval aminoglycoside dosing. Here, we report a retrospective evaluation of morbidly obese patients receiving gentamicin or tobramycin at our hospital. The objective of this study was to evaluate the accuracy of the commonly recommended adjusted weight for weight-based dosing. There were 31 morbidly obese patients who received gentamicin or tobramycin 5–7 mg/kg every 24 hours using a 40% dosing weight correction factor. Our institution utilizes 16-hour postdose concentrations to monitor extended interval aminoglycosides. Twenty-two of the 31 patients (71%) achieved an appropriate serum drug concentration. Four patients (13%) were found to be supratherapeutic and 5 patients (16%) subtherapeutic. The only variable that correlated with supratherapeutic levels was older age (P=0.0378). Our study helps to validate the current dosing weight correction factor (40%) in the morbidly obese population. We recommend caution when dosing aminoglycosides in morbidly obese patients who are of older age.